APLIKASI KLINIS RETIKULOSIT - Suega, Ketut (journal of internal medicine, 2012)
Reticulocytes are immature nonnucleated erythrocytes that are released from the bone marrow following enucleation of the normoblast. Under the in! uence of erythropoietin, committed erythroid progenitor cells divide and differentiate through a series of stages, giving rise basophilic normoblasts, polychromatophilic normoblasts, and orthochromic normoblastsin sequence. Reticulocytes are similar to mature red blood cells, except that they retain functioning polyribosomes and continue to synthesize hemoglobin. Because the reticulocyte stage of erythroid differentiation only lasts a few days, the number of reticulocytes in the blood is a useful clinical indicator of the rate of erythropoiesis. Reticulocytes exist in the circulation for only 1 ? 2 days and signal the marrow erythropoietic activity 3 ? 4 days after iron was actively incorporated into haemoglobin. Early changes in reticulocyte count may simply re! ect the release of immature reticulocytes from the marrow rather than the true expansion of erythropoiesis. Reticulocyte counts have once again acquired great interest and importance following the introduction of instruments that use dyes speci" c for RNA. This has resulted in precise and accurate counts even at low reticulocyte concentrations The latest generation of automated analyzer provides additional information on reticulocytes, such as the immature reticulocyte fraction (IRF) and other reticulocyt indices, eg, mean reticulocyte volume (MCVr) and mean reticulocyte haemoglobin content (CHr). To date, the most widely studied of the reticulocyte indices is the CHr. The hemoglobin content is considered to be constant throughout the lifetime of erythrocytes and circulating reticulocytes1 unless structural changes take place that compromise the amount of cytoplasm or cause cellular fragmentation. The normal value for the ! owcytometry method can range from 1% to 2% depending on the cut off point used to separate reticulocytes from the normal red blood cell population. Since reticulocyte enumeration provides information about the bone marrow activity and the effectiveness of red blood cell production, it is crucial in the clinical application of reticulocytes parameters to aid the diagnosis of anemic patients, and for monitoring bone marrow transplantation patients, patients undergoing therapy with marrow toxic drugs, and patients being treated for anemia
Keywords: flowcytometry, reticulocytes, clinical applications